TEACHERS’ ATTITUDES TOWARDS USING YOUTUBE VIDEO TO ENHANCE LISTENING COMPREHENSION - Arbain, Muhammad; Novika, Hartatya (STIT Ibnu Rusyd Tanah Grogot, 2022)
The development and condition of the current pandemic has changed the direction of learning from face-to-face to online. The main purpose of this research study is to bring out one of the World Wide Web’s most important sites which is YouTube and show its ability to evolve listening comprehension of EFL learners. This research aims to teachers’ attitudes towards using YouTube video to enhance listening comprehension. Questionnaire is handed to teachers who have an experience with the oral expression module from the English Department. The data are gathered and analysed in order to see positive or negative attitude from teachers towards using YouTube videos as means to enhance the learners’ listening comprehension. The findings show that teachers have a positive attitude towards the internet in general and the use of YouTube videos as a means to develop listening comprehension. This research can provide better ways for teaching and learning and create a new space for obtaining new experiences particularly for teachers.